Living Qur’ân: Fadhîlah Surah al-Mulk dalam Tafsir Ibnu Katsîr (Kajian terhadap Tradisi dalam Membaca Surah al-Mulk Ba’da Maghrib di Pondok Pesantren Dârul ‘Ulûm Muara Mais Jambur Kabupaten Mandailing Natal) - Muhammad, Muhammad; Indra, Ahmad Perdana; Halimah, Halimah (Al-I'jaz: Jurnal Kewahyuan Islam, 2020)
Alquran is the word of Allah which contains teachings and life guidance for Muslims. Such a function makes the students of the Islamic Boarding School Dârul 'Ulûm Muara Mais Jambur in Mandailing Natal Regency carry out the tradition of reciting Surah al-Mulk every day after performing the Maghrib prayer in congregation. This tradition is a suggestion from H. Mawardi Lubis Addary, the Headmaster (Mudîr) of the Islamic Boarding School. This tradition has a very positive value and deserves to be preserved. Therefore, the author considers it important to write a study entitled "Living Qur'ân: The Superiority of The Surah al-Mulk in Ibn Katsir's Tafsir (Study of Traditions in Reading Surah al-Mulk Ba'da Maghrib at Islamic Boarding School Dârul 'Ulûm Muara Mais Jambur in Mandailing Natal Regency)”.  Fast traslate Icon translate     Fast traslate Icon translate     Fast traslate Icon translate